Morphology and Moleculer Sequencing Bactrocera sp. Fruit Fly from Deli Serdang District - Sari, Putri Mustika; Lisa, Oviana; Weihan, Rayhan Amadius (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
Due to some doubts regarding the morphological identification of fruit flies, molecular identification is necessary to more clearly determine the origin of the insect. With the PCR RAPD method, which can identify genetic markers, it can effectively and quickly distinguish closely related species. RAPD is used as a tool to create genetic maps, identify strains, species, populations, and systematics of various organisms. RAPD can differentiate laboratory populations that are morphologically indistinguishable. So the purpose of this study is to more clearly determine the identity of the fruit flies found, both morphologically and molecularly. This research method is a purpose sampling method, where fruit fly samples are obtained from traps using attractants in red guava plantations. The fruit fly species found in the red guava plantation location are Bactrocera sp., and Bactrocera kinabalu. The results of the study found that the fruit fly species Bactrocera sp. found in the village of Sawit Rejo was identified morphologically as having many similarities with Bactrocera papayae except for its abdominal pattern. To confirm the taxonomic status of Bactrocera sp. For further clarification, it is necessary to use molecular identification of cytochrome oxidase 1 and phylogenetic genes, with DNA sequencing results (500 bp) showing that the Bactrocera sp. species has a homology level of 88% with Bactrocera carambolae from the Genbank collection. The phylogenetic tree shows that Bactrocera sp. has ancestors from China.